Crustal-scale fault systems in the Korean Peninsula unraveled by reflection seismic data - Final stack results and example receiver gathers from South Korea seismic reflection campaign in 2021 - Zappalà, Samuel (Uppsala University, 2022)
Resulting data from the 2021 campaign in the Seoul metropolitan area (South Korea). Around 40 km of high-resolution reflection seismic data were acquired along an E-W profile cross-cutting major crustal scale fault systems. The raw data were obtained with 2 seismic vibrators as source and 421 10 Hz geophones as receivers, with an asymmetric split spread and roll-along geometry. The acquired data has been processed with Globe Claritas software and it is provided in a standard seg-y format.

A full description of the data aquisition is provided in:

Samuel Zappalá, Alireza Malehmir, Tae-Kyung Hong, Christopher Juhlin, Junhyung Lee, Myrto Papadopoulou, Bojan Brodic, Seongjun Park, Dongchan Chung, Byeongwoo Kim, & Jeongin Lee. Crustal-scale fault systems in the Korean Peninsula unraveled by reflection seismic data, Earth and Space Science, submitted

However, the methodology is the same as used in the previous study:

Malehmir, A., Hong, T.-K., Lee, J., Zappalá, S., Brodic, B., Chung, D., Kim, B., Park, S., Lee, J., & Kil, D. (2022). Fault intersections control short period intraplate start-stop seismicity in the Korean Peninsula. In Tectonophysics (No. 229387; Vol. 834). https://doi.org/10.1016/j.tecto.2022.229387

In the dataset are present:
- 2 examples of receiver gathers raw: (korea2021_P3_rec1185_raw.segy and korea2021_P3_rec487_raw.segy).
- the same 2 receiver gathers after the applied processing: (korea2021_P3_rec1185_raw_rfst_fils_res_tm.segy and korea2021_P3_rec487_raw_rfst_fils_res_tm.segy).
- stack section acquired with wireless receivers (20 m spacing), unmigrated and migrated:(korea2021_P3_stack.segy and korea2021_P3_migrated.segy).
- stack section acquired with wireless receivers (20 m spacing) with an applied cross dip correction for 10 degrees towards north, unmigrated and migrated: (korea2021_P3_crossdipcorrected_stack.segy and korea2021_P3_crossdipcorrected_migrated.segy).
- unmigrated stack section acquired with landstreamer receivers (2 m spacing): (korea2021_P3_streamer_stack.segy.

Resultatdata från reflektionsseismiska 2021-kampanjen i Seouls storstadsområde (Sydkorea).

Se engelska beskrivningen för en översikt av filerna.
Förkastningssystem i jordskorpan på den koreanska halvön belyst av seismiska reflektionsdata - Slutliga stackresultat och "receiver gathers" exempel från Sydkoreas seismiska reflektionskampanj 2021
Keywords: SEISMIC PROFILE; geological faults; south korea; Geophysics; Geofysik